THE EFFECT OF SPACE ENVIRONMENTS FACTORS ON SPACECRAFT STRUCTURE (Journal of Engineering, 2003)
This work covers the investigation of the effects of space environments factors on spacecraft structure. The satellite operates on a low earth orbit at circular (500,500) km, and subjected to different torques in space environments.The purpose of this paper is to develop the satellite structure design and test it to obtain the mechanical behaviour of structure. The satellite used so far is spin - stabilized, and rotating about one axis in 3 rpm. A configuration to the structure is suggested to be hexagonal; the dimension of structure is 110cm in diameter and 85cm high. The general static and dynamics tested of the system are verified, and analyzed to find the stress,strain, and vibration on the structure.